Structural variants of AcrIIC5 inhibit Cas9 via divergent binding interfaces - Hong, Sung-Hyun; An, So Young; Park, Changkon; Kim, Youngim; Kim, Eun-Hee; Kim, Nak-Kyoon; Suh, Jeong-Yong (Cell Press, 2025)
CRISPR-Cas is a bacterial defense system that employs RNA-guided endonucleases to destroy invading foreign nucleic acids. Bacteriophages produce anti-CRISPR (Acr) proteins to evade CRISPR-Cas defense during the infection. AcrIIC5, a type II-C Cas9 inhibitor, exhibits unusual variations in the local backbone fold between its orthologs. Here we investigated how the folding variations affect the inhibition of target Cas9 using AcrIIC5 orthologs. Structural comparison of free AcrIIC5Smu and AcrIIC5Nch confirmed that the folding variation correlated with characteristic indels in the helical region. Mutagenesis and biochemical assays combined with AlphaFold2 predictions identified key residues of AcrIIC5 orthologs important for Cas9 inhibition. Remarkably, AcrIIC5 orthologs employed divergent binding interfaces via folding variations to inhibit the Cas9 targets. Our study suggests that Acr proteins have evolved structural variants to diversify key interfaces for target Cas9, which could be beneficial for the adaptation of phages to evasive mutations on the Cas9 surface.